Fast and specific detection of the invasive forest pathogen Heterobasidion irregulare through a Loop‐mediated isothermal AMPlification (LAMP) assay. Issue 2 (31st October 2017) - Sillo, F.; Giordano, L.; Gonthier, P.
Summary: Heterobasidion irregulare is one of the most destructive fungal pathogens of pines in North America and was accidentally introduced into central Italy, where it has become invasive. The fungus is currently recommended for regulation by the European and Mediterranean Plant Protection Organisation (EPPO). In this work, an efficient diagnostic tool for the early detection of H. irregulare based on Loop‐mediated isothermal AMPlification (LAMP) coupled with two different DNA extraction methods was developed. The LAMP assay showed high specificity and good sensitivity, with a limit of detection of about 20 picograms of target DNA and time of detection of less than 40 min. The assay was successfully tested on a variety of different samples, including fungal fruiting bodies, infected plants and colonized wood. A survey on environmental samples collected in the field was also performed using the LAMP assay coupled with a rapid DNA extraction method. The possible applications of this molecular diagnostic tool encompass the monitoring of pine forests surrounding the current invasion area, laboratory or in‐field analyses of samples from suspected trees, and the surveillance in the ports of entry of wood imported from North America.